Pedagogical Management of Civil Education of Research Universities Students - Yepaneshnikov, Vladimir V.; Pugacheva, Natalya B.; Goloshumova, Galina S.; Kuznetsova, Veronika V.; Dobrovolskaya, Liana V.; Moiseeva, Liudmila V.; Garaganov, Artur V.; Litvinenko, Ninel A. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the contradictory interaction of Western and Eastern civilizations and the need of society in preparing of professionals who are not only competitive in the labor market, but also aware of the responsibility for the implementation of civil rights and duties and are able to fulfill their civic duty. The purpose of the article is to identify the characteristics of the pedagogical management of civil education of research universities’ students. The leading method is the method of action research (AR), allowing to obtain new knowledge about the pedagogical management of process of civil education of students, aimed at formation of sustainable civil qualities and characterizing their speakers as entities of legal, moral, political, social and economic relations in state-public education. The article reveals the essence and function (cognitive, ethical humanist, cognitive) of students’ civic education; clarifies the contents of civic education; determines the pedagogical conditions of students’ civil education (the formation of civic consciousness, the development of civic initiative and civic responsibility and participation in civic activities). Article Submissions may be useful for teachers of research universities; for centers of personnel training and retraining in the selection and structuring of the content of professional development of the research universities’ teaching staff. Keywords: Research Universities, Functions of Civic Education, Civic Consciousness, Pedagogical Management. JEL Classifications: I21, I23, Z13